Some Aspects of Mutual Relationship Between Land and Housing Law in Market Economy - P. A. Politakhin (Сибирское юридическое обозрение, 2011)
The author analyses current state of available housing in Russia and accessibility of housing to Russians. The authors draws attention to the problems that economically disadvantaged families encounter when they are given free land plots for private housing construction and accommodation building. As a conclusion the author recommends to lower costs of accommodation building and communal services as well as to develop housing business.